HCFC1 loss-of-function mutations disrupt neuronal and neural progenitor cells of the developing brain - Jolly, Lachlan A; Nguyen, Lam Son; Domingo, Deepti; Sun, Ying; Barry, Simon; Hancarova, Miroslava; Plevova, Pavlina; Vlckova, Marketa; Havlovicova, Marketa; Kalscheuer, Vera M; Graziano, Claudio; Pippucci, Tommaso; et al. (Human molecular genetics, 2015)
Both gain- and loss-of-function mutations have recently implicated HCFC1 in neurodevelopmental disorders. Here, we extend our previous HCFC1 over-expression studies by employing short hairpin RNA to reduce the expression of Hcfc1 in embryonic neural cells. We show that in contrast to over-expression, loss of Hcfc1 favoured proliferation of neural progenitor cells at the expense of differentiation and promoted axonal growth of post-mitotic neurons. To further support the involvement of HCFC1 in neurological disorders, we report two novel HCFC1 missense variants found in individuals with intellectual disability (ID). One of these variants, together with three previously reported HCFC1 missense variants of unknown pathogenicity, were functionally assessed using multiple cell-based assays. We show that three out of the four variants tested result in a partial loss of HCFC1 function. While over-expression of the wild-type HCFC1 caused reduction in HEK293T cell proliferation and axonal growth of neurons, these effects were alleviated upon over-expression of three of the four HCFC1 variants tested. One of these partial loss-of-function variants disrupted a nuclear localization sequence and the resulting protein displayed reduced ability to localize to the cell nucleus. The other two variants displayed negative effects on the expression of the HCFC1 target gene MMACHC, which is responsible for the metabolism of cobalamin, suggesting that these individuals may also be susceptible to cobalamin deficiency. Together, our work identifies plausible cellular consequences of missense HCFC1 variants and identifies likely and relevant disease mechanisms that converge on embryonic stages of brain development.
Keywords: buněčná diferenciace; faktor C1 hostitelské buňky; Amino Acid Substitution; mozek; exprese genu; Humans; Gene Expression; Transduction, Genetic; Female; mutace; Neural Stem Cells; lidé; HEK293 Cells; zvířata; proliferace buněk; myši; Cells, Cultured; mentální retardace; aktivní transport - buněčné jádro; transdukce genetická; Mice; transportní proteiny; RNA, Small Interfering; oxidoreduktasy; nervové kmenové buňky; Amino Acid Sequence; Carrier Proteins; Pedigree; malá interferující RNA; rodokmen; Host Cell Factor C1; ženské pohlaví; Intellectual Disability; Male; substituce aminokyselin; Brain; HEK293 buňky; kultivované buňky; Cell Proliferation; Cell Differentiation; RNA Interference; Active Transport, Cell Nucleus; Animals; Mutation; mužské pohlaví; Oxidoreductases; RNA interference; sekvence aminokyselin